1991
DOI: 10.1073/pnas.88.21.9799
|View full text |Cite
|
Sign up to set email alerts
|

Delta, a transcription factor that binds to downstream elements in several polymerase II promoters, is a functionally versatile zinc finger protein.

Abstract: The promoters of several eukaryotic genes transcribed by RNA polymerase H contain elements located downstream of the transcriptional start site. To gain insight into how these elements function in the formation of an active transcription complex, we have cloned and sequenced the cDNA that encodes 8, a protein that binds to critical downstream promoter elements in the mouse ribosomal protein rpL30 and rpL32 genes. Our results revealed that the 6 protein contains four C-terminal zinc fingers, which are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
221
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(228 citation statements)
references
References 31 publications
(20 reference statements)
6
221
0
Order By: Relevance
“…As a first step toward a precise description of this promoter element, in this study we identified the ubiquitous factor TPF as the transcription/initiation factor YY1. This 414-amino-acid Krüppel-like protein with four C 2 H 2 -type zinc fingers was cloned independently and in different contexts by four groups some years ago and is also referred to as ␦, NF-E1, and UCRBP (15,19,42,51). In the meantime, binding sites for YY1 have been identified in many promoters, indicating that this factor may be of general importance for transcription initiation from a substantial number of promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step toward a precise description of this promoter element, in this study we identified the ubiquitous factor TPF as the transcription/initiation factor YY1. This 414-amino-acid Krüppel-like protein with four C 2 H 2 -type zinc fingers was cloned independently and in different contexts by four groups some years ago and is also referred to as ␦, NF-E1, and UCRBP (15,19,42,51). In the meantime, binding sites for YY1 have been identified in many promoters, indicating that this factor may be of general importance for transcription initiation from a substantial number of promoters.…”
Section: Discussionmentioning
confidence: 99%
“…YY1 (also called ␦, NF-E1, and UCRBP) is a 414-amino-acid Krüppel-like protein (15,19,42,51) that represses a variety of cellular as well as viral promoters but can also activate the expression of other genes (see reference 22 for further references), hence the designation YY1 (yin and yang 1). YY1 can also direct accurate basal transcription in vitro through the initiators of the cytochrome c oxidase subunit Vb promoter (4) and the adeno-associated virus (AAV) type 2 P5 promoter (50).…”
mentioning
confidence: 99%
“…YY1 is a zinc finger transcription factor first discovered for its function in viral gene expression (20,21) and cloned during investigations of viral (22), immunoglobulin (23), and ribosomal (24) gene expression. YY1 has since been implicated in a number of processes, including development of muscle (25)(26)(27)(28)(29)(30) and B cells (31)(32)(33), and stem cell regulation (34)(35)(36)(37).…”
mentioning
confidence: 99%
“…A large number of cellular and viral genes have been shown to be negatively regulated by YY1 (for reviews, see [31,34]). Examples of genes positively regulated by YY1 include c-myc [35], some ribosomal protein genes [36] and p53 [37].…”
Section: Discussionmentioning
confidence: 99%